2023
DOI: 10.3390/land12051003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Coordinated Evolution Mechanism of Regional Sustainable Development and Tourism in China’s “Beautiful China” Initiative

Abstract: As the world’s largest developing country, China first proposed the construction of a Beautiful China initiative in 2012, with the aim of exploring Chinese solutions for sustainable regional development. The construction of a beautiful China is based on the guiding ideology of the Five-sphere Integrated Plan in China, that is, the overall plan for building socialism with Chinese characteristics, including economic construction, political construction, cultural construction, social construction and ecological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…We concluded that the following features characterize the PPDC model for tourism safety evaluation and early warning: (1) Clear mathematical meaning of Equation (8), which clearly shows that the samples are divided into K classes, and the samples in different classes are separated as much as possible. In contrast, samples in a class are as dense as possible.…”
Section: Characteristics Of the Ppdc Model Comparison With The Other ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that the following features characterize the PPDC model for tourism safety evaluation and early warning: (1) Clear mathematical meaning of Equation (8), which clearly shows that the samples are divided into K classes, and the samples in different classes are separated as much as possible. In contrast, samples in a class are as dense as possible.…”
Section: Characteristics Of the Ppdc Model Comparison With The Other ...mentioning
confidence: 99%
“…It has become a critical driving force for achieving sustainable development in recent years [1][2][3][4][5]. Also confirmed by the UNWTO (United Nations World Tourism Organization), the tourism industry plays a pivotal role in promoting sustainable development [6][7][8]. The UNWTO clearly states the following: (1) Tourism has the potential to contribute, directly or indirectly, to all of the 17 sustainable development goals in the 2030 Agenda for Sustainable Development; (2) Tourism has mainly been included as targets in Goals 8, 12, and 14 on inclusive and sustainable economic growth, sustainable consumption and production, and the sustainable use of oceans and marine resources, respectively; (3) Sustainable tourism is firmly positioned in the 2030 Agenda for Sustainable Development [7].…”
Section: Introductionmentioning
confidence: 99%
“…Shaanxi's tourism industry has always been a significant pillar industry. To accomplish the coordinated development of the tourism economy and ecological environment, it is still necessary to pay attention to the coordinated effect of transport and tourism development and its influencing factors [26]. To further promote the coordinated development of the tourism economy and ecological environment, the relevant authorities in Shaanxi should continue to strengthen the construction of transport infrastructure, improve tourism services, and prioritise environmental protection, the protection of natural resources, and the preservation of cultural heritage.…”
Section: Coordinated Development Of Regional Tourismmentioning
confidence: 99%
“…At the same time, the number of employees reached 52.8294 million, an increase of over 10 million compared to 2012; The population urbanization rate has reached 64.72%, an increase of 11.62% compared to 2012. Therefore, the construction industry has made important contributions to China’s economic growth 3 , social employment, urbanization 4 , and other aspects. However, with a booming construction market, issues such as imbalanced regional development, poor quality of development, and ineffectiveness, came up.…”
Section: Introductionmentioning
confidence: 99%